2021
DOI: 10.1177/0734242x21998730
|View full text |Cite
|
Sign up to set email alerts
|

Reverse supply chain conceptual model for construction and demolition waste

Abstract: Construction and demolition waste (CDW) substantially contributes to environmental degradation because of its intrinsic characteristics of fast and high generation volume, low recycling rate, and low revenue margins. A systemic problem is that recycling facilities are not usually a part of a reverse supply chain (RSC) specific for CDW. This makes the recovery process costs prohibitive, especially where companies are unable to receive and process large volumes of waste continuously. This paper presents a system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 63 publications
(168 reference statements)
0
39
0
Order By: Relevance
“…This research adopts a mixed philosophical stance that combines interpretivism [96][97][98] and pragmatism [99]. As an epistemological stance, interpretivism was adopted in order to critically review extant literature and generate questions that then informed the ensuing inductive research approach, which sought to generate new theory on "negotiation" as a viable procurement path [100].…”
Section: Methodsmentioning
confidence: 99%
“…This research adopts a mixed philosophical stance that combines interpretivism [96][97][98] and pragmatism [99]. As an epistemological stance, interpretivism was adopted in order to critically review extant literature and generate questions that then informed the ensuing inductive research approach, which sought to generate new theory on "negotiation" as a viable procurement path [100].…”
Section: Methodsmentioning
confidence: 99%
“…While adding a different perspective to Brandão et al (2021b), this study found that state government organizations via regulating, monitoring, leading and incentivizing employ an information-centric influence over the QA in RLSC of DW. The strategies mentioned by Brandão et al (2021b), such as legislation, penalties and fines and landfill disposal fees, were discussed in the current study under the umbrella strategy of “regulating”. The state government organizations' influence as a regulator was the most frequently mentioned strategy in the interviews, reflecting that QA in RLSC becomes information-rich within a regulatory framework.…”
Section: Discussionmentioning
confidence: 84%
“…It is well popular that the regulatory pressures from the government are the critical impetus to promote sustainability in the CI all around the world (Ahmed et al , 2019; Liu et al , 2020; Singh and Sushil, 2021). Through a systematic literature review, Brandão et al (2021b) claimed that the government emerges as the most influential actor of the RLSC of DW, being the only stakeholder employing six influence strategies: legislation, penalties and fines, inspection, subsidies, landfill disposal fee and incorporating reprocessed products using public construction works. While adding a different perspective to Brandão et al (2021b), this study found that state government organizations via regulating, monitoring, leading and incentivizing employ an information-centric influence over the QA in RLSC of DW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…reputation for being wasteful, unsustainable and a major pollutant (Brandão et al, 2021), accompanied by unsatisfactory outcomes for project participants and wider society alike (Newman et al, 2020;Nikmehr et al, 2021). Construction productivity, in contrast to other sectors, has not grown over the last 30 years (Teicholz, 2013;Fathalizadeh et al, 2021).…”
mentioning
confidence: 99%